La herencia cultural latinoamericana como poética docente - Marcipar, Matías (Universidad Nacional del Litoral, 2020)
Teaching practices are sustained in poetics, which narrations give meaning to teaching and provide criteria for the selection of content. The MPL (Latin American Popular Music) has its presence in curricular texts, but its curricular evolution largely depends on those who are mobilized by a Latin American poetics in education. In turn, the very concept of a teaching poetic that seeks to give life to the Latin American cultural heritage presents an enormous margin of ambiguity. From the concrete context and experience of the CREI secondary school specializing in live popular music, the article tries to problematize the issue in its different edges, proposing a brief historical review of institutional roles and political-educational positions in relation to culture.